(untitled) (Patan Prospective Journal, 2025)
The study examines qualitative research design that has grown more important in investigating the intricacies of teaching and learning in computer education. In contrast to quantitative methods that focus on measuring specific variables, qualitative approaches offer detailed, contextual insights into students’ experiences, teachers’ instructional methods, classroom interactions, and the socio-cultural influences that affect learning. This article explores the importance, techniques, advantages, and obstacles of qualitative research design in computer education’s teaching and learning processes. This research indicates that qualitative approaches like interviews, observations, focus groups, and document analysis, are especially useful for grasping learners’ views, pinpointing obstacles to digital literacy, and improving teaching methods. The research finds that qualitative stsudies are crucial for enhancing computer education particularly in Nepal and generally in the global education system especially in order to cope with the changing digital environments. The status of computer education in Nepal has been explored a bit complicated compared to that of India, a neighboring country that is digitally booming.